2016
DOI: 10.1016/j.ejrad.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT volumetric measurement with RECIST response in patients with lung cancer

Abstract: Purpose To examine the correlations between uni-dimensional RECIST and volumetric measurements in patients with lung adenocarcinoma and to assess their association with overall survival (OS) and progression-free survival (PFS). Materials and Methods In this study of patients receiving chemotherapy for lung cancer in the setting of a clinical trial, response was prospectively evaluated using RECIST 1.0. Retrospectively, volumetric measurements were recorded and response was assessed by two different volumetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 49 publications
2
40
0
4
Order By: Relevance
“…Our results demonstrated that the total tumor volume and mean tumor density obtained using volumetric measurements correlated better with PFS than tumor size of RECIST 1.1. Similar results have been reported elsewhere [ 18 , 25 ]. Hayes et al reported superiority of volumetric measurements over use of unidimensional RECIST criteria to predict overall survival [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrated that the total tumor volume and mean tumor density obtained using volumetric measurements correlated better with PFS than tumor size of RECIST 1.1. Similar results have been reported elsewhere [ 18 , 25 ]. Hayes et al reported superiority of volumetric measurements over use of unidimensional RECIST criteria to predict overall survival [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have been reported elsewhere [ 18 , 25 ]. Hayes et al reported superiority of volumetric measurements over use of unidimensional RECIST criteria to predict overall survival [ 25 ]. Welsh et al also suggested volumetric analysis as the preferred method to detect tumor progression [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…For example, some studies have shown discordance between response criteria and volume measurements in the classification of tumour response assessment. 27,28 While some have found that 3D or volumetric measures for tumour response appear to be the superior method, 16,[29][30][31][32] other authors have shown no difference in comparison to unidimensional measurements, and thus careful attention to the clinical scenario or application, as well as further validation and correlation with outcomes is needed to establish this resource-intensive measurement technique.…”
Section: Response To Therapymentioning
confidence: 99%
“…Accurate radiological assessment for predicting therapeutic responses and clinical outcomes of non-small cell lung cancer (NSCLC) is important in clinical practice and drug development trials 1 . Cancers have uneven growth patterns, and even within single tumors specific areas may increase in size while other portions remain stable.…”
Section: Introductionmentioning
confidence: 99%